Anthropological interference on the vegetation of Wassaniya Forest Reserve In Sokoto, Nigeria - Muhammad, Atiku (2017)
A forest inventory was carried out to investigate the anthropological interference on the vegetation of Wassaniya Forest Reserve in Sokoto state of northwestern Nigeria. Two approaches were employed. Firstly Landsat Multispectral Scanner (MSS) of 1986 (17- 07-1986) and Landsat 8 Operational Land Imager Thermal Infrared Sensor (OLI-TIRS) of 2015 (0-07-2015) were used to capture images of the respective time of the same study area. The image data were analyzed within Idrisi Taiga environment using Markov change analysis. The Land Use Land Cover (LULC) changes of both dates 1986 and 2015 were detected to gain an insight into the changes in LULC and to make predictions for the future (2030). Secondly, a participatory rural approach was conducted using inclusion and exclusion criteria by administering questionnaires within twelve communities residing around the study area. A multi-stage random sampling technique was adopted for selecting 120 respondents, from three (3) villages out of two (2) districts each in two local government areas of Sokoto State. Result shows that out of the 1,396 individual trees encountered, 46 species were identified belonging to 19 family groups. Fabaceae has the highest number of species with 13, while Guiera senegalensis and Combretum micrantum recorded the highest number of frequency of occurrence which is 575 and 410 respectively. Acacia nilotica and Faretia apondanthera were among the least with only one (1) representation. Parkia biglobosa has the highest diameter at breast height (200cm), tree height (48m) and basal area (2.11m3). smallest DBH was recorded by Annona senegalensis (14cm), while the smallest tree height was recorded by Faretia apondanthera (4m) and the lowest basal area was recorded by Acacia nilotica (0.02m3). The highest above ground biomass estimated was recorded by Mitragyna inermis (5,379 kg) and the lowest was from Grewia mollis (25 kg). With regards to LULC study, the maximum likelihood classification revealed an accuracy of 86.25%. The results reveal eight different (LULC) vegetation types based on different conditions and other site characteristics; dense forest, scrubland, shrubby area, open grassland, and farmland. Others are dense forest (partly scrubland), dense forest (partly open grassland) and scrubland (partly open grassland). Change detection between the vegetation types has indicated that dense forest has deteriorated in favor of farmland with a net loss of 100.59ha. It also shows that farmland has increased from 2,061 ha in 1986 to 7,336.53ha in 2015 which indicates a wide reduction of the forested area due to the pressure mounted by agricultural activities. Further predictions by 2030 reveal that farmland will increase by 11.88%. Results from participatory rural appraisal, showed that 39% of the respondents were youth and 80% of them are polygamous which could be the reason why they have large families as 82% of the respondents has 6-20 members. Their level of education was very low, with only 32% attaining primary education. They have a low level of income because 71% (of the respondents) gain less than USD 157 per month. Their consumption of staple food by far exceeds their production, of which out of 43.4% that consume 1120 bags of staple food, only 13% were able to produce enough food while the remaining 20.4% have to embark on other secondary occupations in order to feed their families. The secondary occupations includes; collection and selling of fuelwood (where 78%) of the respondent uses wood and charcoal as fuel), illegal hunter, seller of non-timber forest products, herder of livestock, carver and blacksmith. All this invariably explain the dependency of the rural inhabitants on the forest reserve, which in turn are responsible for forest degradation, deforestation, and desertification. It is therefore recommended that these local communities are given environmental education on the importance of forest conservation, and empower to carry-out environmental related programs, so that they are able to strengthen their livelihood. The dwindling forest reserves shall be enriched, and some of the farmlands shall be converted into forest plantations in order to reduce the total dependency on the forest reserve.